CircHmbox1 Targeting miRNA-1247-5p Is Involved in the Regulation of Bone Metabolism by TNF-α in Postmenopausal Osteoporosis - Liu, Zhuochao; Li, Changwei; Huang, Ping; Hu, Fangqiong; Jiang, Min; Xu, Xing; Li, Bin; Deng, Lianfu; Ye, Tianwen; Guo, Lei (Frontiers in Cell and Developmental Biology, 2020)
Tumor necrosis factor-alpha (TNF-α) increases osteoclasts differentiation to enhance bone resorption and inhibits osteoblasts differentiation to impair bone formation, which play a central role in the pathogenesis of postmenopausal osteoporosis (PMOP). Recent studies implicated an important role of circular RNAs (circRNAs) in osteoporosis. The purpose of this study is to investigate whether circRNAs might be implicated in TNF-α-regulated osteoclasts differentiation and osteoblasts differentiation in PMOP. QRT-PCR was performed to detect expression of circRNA-circHmbox1 and miR-1247-5p in TNF-α-induced osteoclasts differentiation. Western blot, TRAP staining, alkaline phosphatase staining, alizarin red S staining, transwell and cell transfection were conducted to confirm that TNF-α inhibited osteoblasts differentiation by the exosomal with low circHmbox1 expression from osteoclasts. Bioinformatics analysis and luciferase reporter were used to reveal the mechanisms of the circHmbox1/miR-1247-5p/Bcl6 interaction. In this study, we found that the level of circRNA-circHmbox1 was obviously decreased in the induction of osteoclasts differentiation by TNF-α in vivo and in vitro. CircHmbox1 could inhibit RANKL-induced osteoclasts differentiation primarily through binding to microRNA-1247-5p. TNF-α decreased osteoblasts differentiation by the exosomal with low circHmbox1 expression from osteoclasts. Mechanistic studies showed that microRNA-1247-5p regulated osteoclasts differentiation and osteoblasts differentiation by targeting B cell lymphoma 6, which was confirmed to play opposite roles in osteoblasts differentiation and osteoclasts differentiation. Our results provide evidence that circHmbox1-targeting miR-1247-5p is involved in the regulation of bone metabolisms by TNF-α in PMOP.